Blood Pressure Variability in Children With Primary vs Secondary Hypertension. Issue 6 (25th April 2014) - Leisman, Daniel; Meyers, Melissa; Schnall, Jeremy; Chorny, Nataliya; Frank, Rachel; Infante, Lulette; Sethna, Christine B.
<x xml:space="preserve">Abstract</x> Increased blood pressure variability (BPV) is correlated with adverse cardiovascular (CV) events in adults. However, there has been limited research on its effect in the pediatric population. Additionally, BPV differences between primary and secondary hypertension (HTN) are not known. Children with primary and secondary HTN underwent 24‐hour ambulatory blood pressure monitoring and echocardiography studies. BPV measures of standard deviation (SD), average real variability (ARV), and range were calculated for the 24‐hour, daytime, and nighttime periods. Seventy‐four patients (median age, 13.5 years; 74% boys) were examined, 40 of whom had primary HTN. Body mass index z score and age were independent predictors of systolic ARV (R2=0.14) and SD (R2=0.39). There were no statistically significant differences in overall or wake period BPV measures between secondary or primary HTN groups, but sleep period diastolic SD was significantly greater in the secondary HTN group (9.26±3.8 vs 7.1±2.8, P=.039). On multiple regression analysis, secondary HTN was associated with increased sleep period diastolic SD (P=.025). No metrics of BPV in the overall, wake, and sleep periods were found to be significantly associated with left ventricular hypertrophy (LVH). The results of this study do not show a strong relationship between overall or wake BPV with primary vs secondary HTN, but the association of secondary HTN with sleep period diastolic BPV deserves further exploration. Contrary to expectation, the findings of this study failed to indicate a relationship between BPV and LVH for all patients as well for primary hypertensive and secondary hypertensive patients.